The potential application of isoxanthohumol in inhibiting Clostridium perfringens infection by targeting the type IV pili - Zeyu Song; Yanhong Deng; Jichuan Zhang; Zhongmei Wen; Shui Liu; Xuming Deng; Qiaoling Zhang; Qianghua Lv (Microbial Cell Factories)
Abstract Background Clostridium perfringens (C. perfringens) is an important zoonotic pathogen. The diseases such as necrotic enteritis (NE), enterotoxemia, gas gangrene and food poisoning caused by its infection seriously threaten the lives of both humans and animals. However, under the severe situation of antibiotic resistance, the development of new antibacterial strategies or drugs deserves great attention. Results In this study, we selected the virulence factor Type IV pili (TFP) of C. perfringens as the target for drug screening. The gliding motility, biofilm formation, cell adhesion and antibacterial activity of the natural compound isoxanthohumol (IXN) against C. perfringens were determined. Transmission electron microscopy (TEM), TFP gene transcription analysis and Western blot were used to detect the expression of PilA pilin. The therapeutic effect of IXN on C. perfringens infection was demonstrated through a mouse gas gangrene model. It was confirmed that IXN inhibits the function of TFP by down-regulating TFP-encoding genes and two-component regulatory genes. Conclusions In conclusion, our study shows that IXN has the potential to inhibit the function of TFP in C. perfringens and for anti-infection applications.